Circulating (1→3)-β-D-glucan Is Associated With Immune Activation During Human Immunodeficiency Virus Infection. (16th March 2019) - Mehraj, Vikram; Ramendra, Rayoun; Isnard, Stéphane; Dupuy, Franck P; Ponte, Rosalie; Chen, Jun; Kema, Ido; Jenabian, Mohammad-Ali; Costiniuk, Cecilia T; Lebouché, Bertrand; Thomas, Réjean; Coté, Pierre; et al.
Abstract : Plasma levels of fungal antigen (1→3)-β-D-Glucan are elevated during early and chronic human immunodeficiency virus (HIV) infection and do not normalize despite long-term antiretroviral therapy. Such elevation is associated with immune activation in a well-defined cohort of untreated and treated people living with HIV. Abstract: Background: Microbial translocation from the gut to systemic circulation contributes to immune activation during human immunodeficiency virus (HIV) infection and is usually assessed by measuring plasma levels of bacterial lipopolysaccharide (LPS). Fungal colonization in the gut increases during HIV-infection and people living with HIV (PLWH) have increased plasma levels of fungal polysaccharide (1→3)-β-D-Glucan (βDG). We assessed the contribution of circulating DG to systemic immune activation in PLWH. Methods: Cross-sectional and longitudinal assessments of plasma βDG levels were conducted along with markers of HIV disease progression, epithelial gut damage, bacterial translocation, proinflammatory cytokines, and βDG-specific receptor expression on monocytes and natural killer (NK) cells. Results: Plasma βDG levels were elevated during early and chronic HIV infection and persisted despite long-term antiretroviral therapy (ART). βDG increased over 24 months without ART but remained unchanged after 24 months of treatment. βDG correlated negatively with CD4 T-cell count and positively with time to ART initiation, viral load, intestinal fatty acid–binding protein, LPS, and soluble LPS receptor soluble CD14 (sCD14). Elevated βDG correlated positively with indoleamine-2, 3-dioxygenase-1 enzyme activity, regulatory T-cell frequency, activated CD38 + Human Leukocyte Antigen - DR isotype (HLA-DR) + CD4 and CD8 T cells and negatively with Dectin-1 and NKp30 expression on monocytes and NK cells, respectively. Conclusions: PLWH have elevated plasma βDG in correlation with markers of disease progression, gut damage, bacterial translocation, and inflammation. Early ART initiation prevents further βDG increase. This fungal antigen contributes to immune activation and represents a potential therapeutic target to prevent non–acquired immunodeficiency syndrome events.